From Moratorium to One-Channel: Who Governs Indonesian Female Domestic Worker Migration to the GCC? - Bukor,Ester (2025)
This study examines whether formal state authority determines governance zone placement and whether governance zones shift (“zone migration”) across the ANIME stages, Agenda-Setting, Negotiation, Implementation, Monitoring, and Enforcement, in Indonesia’s female domestic worker migration to the GCC. Drawing on qualitative interviews with meso-level actors, it combines the ANIME framework with the Governance Triangle to analyse how authority, capacity, and inclusion shape policy processes. Findings show that while the state holds strong formal authority in agenda-setting, seen in the 2015 moratorium and the SPSK One-Channel Placement System, practical zone placement is shaped by capacity constraints, bargaining asymmetries, and actor exclusion. Both policies migrated from state-centred control to private-sector dominance during implementation and monitoring. The governance triangle appears structurally compressed toward a state-private axis, limiting civil society’s role and weakening accountability. The study extends governance theory by linking structural compression to zone migration and exclusionary dynamics and calls for rebalancing inclusion power and strengthening monitoring capacity. Findings are based on purposive sampling and self-reported accounts, warranting cautious generalisation.
Keywords: Labour migration governance; ANIME framework; Governance Triangle; Zone migration; Indonesia-GCC migration corridor